2015
DOI: 10.1103/physrevd.92.063524
|View full text |Cite
|
Sign up to set email alerts
|

Scale-invariant perturbations in ekpyrotic cosmologies without fine-tuning of initial conditions

Abstract: Ekpyrotic bouncing cosmologies have been proposed as alternatives to inflation. In these scenarios, the universe is smoothed and flattened during a period of slow contraction preceding the bounce while quantum fluctuations generate nearly scale-invariant super-horizon perturbations that seed structure in the post-bounce universe. An analysis by Tolley and Wesley (2007) showed that, for a wide range of ekpyrotic models, generating a scale-invariant spectrum of adiabatic or entropic fluctuations is only possible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 34 publications
1
60
0
Order By: Relevance
“…Refs. [14][15][16][17][18] and references therein). In fact, this is the motivation for having an exotic component in the pre-bounce phase, with an equation-of-state parameter w exotic ≡ P exotic /ρ exotic ≥ 1.…”
Section: Bounce Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Refs. [14][15][16][17][18] and references therein). In fact, this is the motivation for having an exotic component in the pre-bounce phase, with an equation-of-state parameter w exotic ≡ P exotic /ρ exotic ≥ 1.…”
Section: Bounce Stabilitymentioning
confidence: 99%
“…Approaching the bounce from the pre-bounce side, the energy density of such an exotic component "grows to dominate all other forms of energy, including inhomogeneities, anisotropy and spatial curvature" (quote from Ref. [16]). For this reason, we have also considered [4,5] asymmetric versions of the degenerate-metric bounce with w pre-bounce = 1 and w post-bounce ∼ 1/3.…”
Section: Bounce Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a new, especially simple version of ekpyrotic (cyclic) cosmology has been identified that fits all current observations, including nearly Gaussian fluctuations and small r [4][5][6][7]. Also, anamorphic bouncing cosmologies have been introduced that use yet different ways to smooth and flatten the universe during a contracting phase and generate a nearly scale-invariant spectrum of perturbations [8].…”
mentioning
confidence: 91%
“…The occurrence of blueshift scalar perturbation is nonetheless a minor flaw of ekpyrotic theory which can be easily corrected. Hence, new ekpyrotic theory considers multiple scalar field and successfully generated a scalar spectrum which is scale invariant and slightly redshifted [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Producing primordial gravitational waves sourced by the gauge field in the ekpyrotic scenario was also studied in [31].…”
Section: Jhep06(2018)041mentioning
confidence: 99%